Patterns of bisphosphonates utilization in patients under age 45 in a large cohort of commercial insurance beneficiaries in the United States. - Jing Xie; Angela Tong; Seoyoung C Kim (PLoS ONE)
Background The effectiveness and safety of bisphosphonates treatment used in the young population have not been well studied. Despite insufficient data on effectiveness and safety of bisphosphonates in young patients, bisphosphonates are still considered in younger patients at high risk for osteoporosis or fracture. The objectives of this study were to identify bisphosphonate initiators aged 10-45 years and describe their clinical characteristics and to assess time trends of bisphosphonate use over the past decade in a large U.S. population-based cohort. Methods Using the medical and pharmacy claims data from a U.S. commercial insurance (2003-2012), patients aged 10-45 years without malignancy who initiated an oral or intravenous bisphosphonate after at least 1 year of insurance enrollment were selected. Baseline demographics, comorbidities, medications and health care utilization were assessed in the year prior to initiating a bisphosphonate. The trend of bisphosphonate use over time was examined. Results There were 9,082 bisphosphonate initiators (0.02% of the same age group in the population). The mean age was 38.1 years and 79.6% female. Osteoporosis was the most common diagnosis (41.2%). At baseline, 10.8% had a diagnosis of fracture and 29.0% had a bone mineral density measured. Of those who used glucocorticoids (39%) at baseline, the mean 1-year cumulative prednisone-equivalent dose was 2,669 milligrams. The use of bisphosphonates in the young population significantly decreased over the past decade (p<0.001). Conclusions Among young patients aged 10-45, the use of bisphosphonates was uncommon and significantly decreased over the past decade in the U.S. While most patients initiating bisphosphonates had a diagnosis of osteoporosis and fracture in the preceding year, some had no recorded claims with a diagnosis of fracture, osteoporosis, or long-term glucocorticoids use at baseline. Future research is needed to examine the effectiveness and safety of bisphosphonates in young patients at risk for osteoporosis.